Evaluation of Two Primer Sets for Amplification of Comammox Nitrospira amoA Genes in Wetland Soils - Lin, Chenshuo; Xu, Hang; Qin, Wei; Xu, Shaoyi; Tang, Xiufeng; Kuang, Lu; Wang, Xinxin; Jiang, Bin; Chen, Junhui; Shan, Jun; Adams, Jonathan; Qin, Hua; et al. (Frontiers in Microbiology, 2020)
After the discovery of complete ammonia-oxidizing (comammox) Nitrospira, detection and assessments of the contribution of comammox Nitrospira communities to nitrogen cycling are in great demand. PCR-based approach, a common method for the detection of comammox, depends strongly on accurate amplification of the amoA genes from the original DNA samples using appropriate primers. In this study, we reported an evaluation of the performance of two commonly used primer sets, Ntsp-amoA 162F/359R and comaA/B-244f/659r, for amplifying the comammox amoA genes from three representative wetland soils in China [Sangsang (SS), Sanjiang (SJ), and Xianghai (XH)]. Our results demonstrated the two primer sets could both successfully amplify the clades with high relative abundances (RA), and further revealed a broadly similar diversity and community composition of dominant comammox operational taxonomic units (OTUs) (RA ≥ 1%) in each of the three wetland soils. However, the clades with low RA, such as the clade A (1.26%) in SJ and the clade B (11.54%) in XH that were recovered by metagenomics analysis, failed to be amplified using comaA/B-244f/659r, but were successfully amplified and sequenced using Ntsp-amoA 162F/359R. It indicated that, compared to comaA/B-244f/659r, Ntsp-amoA 162F/359R was more sensitive to the clades with low RA. However, it is worth noting that Ntsp-amoA 162F/359R would overestimate the RA of some rare clades. For example, the RAs of clade B in XH were overestimated by 32-fold. Furthermore, high levels of non-target amplification were detected via gel electrophoresis using both primer sets, especially for comammox Clade B amoA genes, implying that we should treat qPCR results based on these primers with caution. Taken together, our study comprehensively compared the performance of the two primer sets on the sensitivity and specificity of amplifying comammox amoA genes in three wetland soils, pointing out the necessity of further development of new primers for the efficient and accurate detection of comammox in various environments.